Kiribati : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
Kiribati is a country in the central Pacific Ocean and one of the least-developed Pacific island economies. A large share of imports and government spending is financed from external grants and fishing license fees. The key policy development has been the adoption of a medium-term strategy, which focuses on reducing the role of the public sector to promote the development of the private sector. The improvement in the current and capital account balances has led to an increase in the overall balance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet